1975
DOI: 10.1007/bf01820688
|View full text |Cite
|
Sign up to set email alerts
|

The Stress Field in the Upper Crust as Determined from In Situ Measurements

Abstract: Zusammen[assungDieser Beitrag behandelt die Spannungsverh~iltnisse in der oberen Erdrinde, so wie sie sich bei Messungen yon lokalen Spannungsfeldern herausstellen, Die Streuung der Daten ist zwar betr~iehtlieh, abet es zeichnen sieh zwei Hauptlinien ab in den Beziehungen zwisehen durchsehnittlieher Horizontalspannung und Tiefe. In alten Grundgebirgen und in den deformierten Gesteinen der Faltungsgebiete findet man im allgemeinen Horizontalspannungen, die gr613er sind als die bereehnete Belastung. In Sediment~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…How do the quantitative results obtained in the present study match the distribution of lineament trends discovered by GUPTA and the corresponding stress fields respectively (ILLIES 1975, RANALLI • CHANDLER 1975, ILLIES & GREINER 1976, JASKOLLA 1978, SCHEIDEGGER 1981)? If we look at the overall rose diagram of the Austrian Part of the Eastern Alps ( fig.…”
Section: Supplementary Notes On Structural Geologysupporting
confidence: 73%
“…How do the quantitative results obtained in the present study match the distribution of lineament trends discovered by GUPTA and the corresponding stress fields respectively (ILLIES 1975, RANALLI • CHANDLER 1975, ILLIES & GREINER 1976, JASKOLLA 1978, SCHEIDEGGER 1981)? If we look at the overall rose diagram of the Austrian Part of the Eastern Alps ( fig.…”
Section: Supplementary Notes On Structural Geologysupporting
confidence: 73%
“…Ranalli & Chandler (1975) compiled stress data from Scandinavia to determine the regional 442 M. FEJERSKOV ET AL. stress field.…”
mentioning
confidence: 99%
“…Sykes and Sbar (1973) determined the earthquake focal mechanisms of 69 intra-plate events and found that in most areas the horizontal stresses are larger than the overburden. These results are confirmed by a comprehensive global compilation of 116 in situ stress magnitude measurements and 59 stress orientations of Ranalli and Chandler (1975). They concluded that (1) in crystalline rock, the horizontal stress magnitudes (minimum S h , maximum S H ) are usually higher than the vertical stress magnitude (S h,H > S V ), (2) in sedimentary basins, the situation is reverse (S h,H < S V ), and (3) in general, the stress field is anisotropic, i.e., stress magnitudes are not equal (S h ≠ S H ≠ S V ).…”
Section: Introductionmentioning
confidence: 57%